Studi Literatur: Peran Pembelajaran Matematika Dalam Pembentukan Karakter Siswa - Husnul Fauzan; Khairul Anshari (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2024)
Mathematics learning has a significant role in student character building, with the main objective of developing logical, rational, critical, creative, systematic, and practical thinking patterns. However, there are still challenges in achieving this goal, such as lack of student interest, learning difficulties, and the availability of adequate resources. This article discusses the role of mathematics learning in students' character building and the importance of integrating mathematics learning with character building. Through a qualitative method with a literature study approach, data were taken from various sources such as journals, books, news, and other scientific research using the Google Scholar database with the keywords mathematics and student character from 2019 to 2024. The results showed that mathematics learning can shape students' character through the development of values such as discipline, honesty, hard work, creativity, curiosity, responsibility, communicative, and independence. Therefore, continuous efforts are needed to improve the quality of mathematics learning, taking into account the needs and interests of students and utilizing available learning technologies and resources. Collaboration between teachers, students, parents and other related parties is also important to create a conducive learning environment that supports students' development in mathematics.